(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Telemedicine has emerged as a transformative solution for improving healthcare accessibility in rural and remote areas worldwide. This study explores the impact of telemedicine on healthcare delivery, patient outcomes, and system efficiency in rural contexts. Using a mixed-methods approach—systematic literature review and case analyses—the research evaluates how digital consultation platforms, remote diagnostics, and AI-driven monitoring have changed medical practices. Results demonstrate improved accessibility, reduced referral times, and cost-effectiveness in patient management. However, infrastructural challenges, digital literacy, and regulatory barriers continue to hinder large-scale adoption. The study concludes with policy recommendations to strengthen telemedicine’s integration into primary healthcare systems.